A study of causes or factor contributing accident at workplace in Northport, Klang / Najwa Fateeha Bakhtiar and Nor Fahmi Adlina Mohamad Fouzi - Bakhtiar, Najwa Fateeha; Mohamad Fouzi, Nor Fahmi Adlina (Faculty of Business and Management, 2013)
Accidents in the workplace occur for a number of reasons. It may result in a minor injury or death. Therefore, employees need to be alert and aware at all times to avoid accidents. Top management such as managers need to know the most common causes of workplace accidents and be able to identify the risk factors early to prevent it. A good working environment may help the organization to run their daily operation smoothly, thus achieve their goals successfully. Safety at the workplace is very important, therefore the Malaysian government has made an effort’s on executing the safety and health policies through the enforcement of guidelines as well as conducting the safety seminars and certifications. However, the existing record indicated that the present Occupational Safety and Health (OSH) situation in the workplace is still very much more poor and below expectation. This paper therefore highlights the issue about the most common causes or factors of workplace accidents among workers at work place. This paper further examined the relationship between the factors that contribute to the workplace accidents and suggested solutions for those issues. After assessing through the homogeneity of the population, the probability sampling was performed in ensuring the reliability of the study. Using 70 samples, correlation investigation was conducted at the operation department. In ensuring the stability of information generated, cross sectional data were conducted using self-administered questionnaire. Based on the result, the researcher concludes that elements like stress and fatigue, workplace layout, lack of training and machineries or tools assumed to directly influence the workplace accident.